Mu’alajat Al-Isyā’āt Fī Wasā`il At-Tawāṣul Al-Ijtimā’i Fī Ḍau`i Al-Qur`ān Al-Karīm: معالجة الإشاعات في وسائل التواصل الاجتماعي في ضوء القرآن الكريم - Abdullah, TM Yusuf Amir; Al-Gumaei, Ammar Mohammed Abdo; Herman, Heggy Fajrianto (Civilization Research: Journal of Islamic Studies, 2023)
This study aims to identify hoaxes and the main factors of their spread through social media and understand their history through Quranic studies, to find out the Quranic attitude towards rumors in the modern era and address them through its verses and interpretations. This research follows a descriptive and analytical approach, and the methods of collecting information in this research are library and documentary research methods. The researcher traced Quranic verses related to hoaxes, collected and interpreted them carefully through books of tafsir, then related them to hoaxes. The researcher also used previous research on the subject with detailed attribution of references to the research and the book. This research proves that hoaxes have a long history, as they have existed since the time of our father Adam and our mother Eve, who were only ordinary humans back then, and their spread has increased in our own time.